ҚАРАҚАЛПАҚСТАН ШАРАЯТЫНДА ИНСАН ҚӘЎИПСИЗЛИГИН ТӘМИЙНЛЕЎ МАШҚАЛАЛАРЫ - Нурланов, А.С. (FAN va JAMIYAT, 2022)
The article discusses the assessment of the consequences of the ecological crisis on the productivity of agricultural products and in the provision of basic food products to preserve the health of the local population in the conditions of Karakalpakstan.